1982
DOI: 10.1104/pp.70.5.1321
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Manganese Superoxide Dismutase from the Higher Plant Pisum sativum

Abstract: A manganese-containin superoxide dismutase (EC 1.15.1.1) was fully characterized from leaves of the higher plant Pisum sativum L., var. Lincoln. The amino acid composition determined for the enzyme was compared with that of a wide spectrum of superoxide dismutases and found to have a highest degree of homology with the mitochondrial manganese superoxide dismutases from rat liver and yeast. The enzyme showed an apparent pH optimum of 8.6 and at 25°C had a maximum stability at alkaline pH values. By kinetic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…This band accounted for 70% of the total activity (calculated from data in Table 1) and was assigned to the MnSOD type (KCN-insensitive, H 2 O 2 -insensitive). However, its electrophoretic mobility (similar to that of plant FeSODs) and apparent molecular mass (45 kDa) are clearly different from those of typical plant MnSODs (Sevilla et al 1982).…”
Section: Composition Of Sod Isozymes In Alfalfa Nodules and Leavesmentioning
confidence: 80%
“…This band accounted for 70% of the total activity (calculated from data in Table 1) and was assigned to the MnSOD type (KCN-insensitive, H 2 O 2 -insensitive). However, its electrophoretic mobility (similar to that of plant FeSODs) and apparent molecular mass (45 kDa) are clearly different from those of typical plant MnSODs (Sevilla et al 1982).…”
Section: Composition Of Sod Isozymes In Alfalfa Nodules and Leavesmentioning
confidence: 80%
“…However, DETCA is a nonspecific metal chelator that may affect the activity of copper-containing enzymes other than SOD1 (Kober et al , 2003; Halliwell and Gutteridge, 2007). It can also bind to other transition metals and has been reported to inhibit a MnSOD (Sevilla et al , 1982). Also, DETCA reduces CM-H 2 DCFDA loading in these cells (supplemental figure 1), likely via binding of the dye to the DETCA thiol.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, in the glyoxysomal matrix Cu,Zn-SOD is present (24) whereas in soluble fractions of leaf peroxisomes Mn-SOD is found instead (24) and, if its activity is not completely inhibited, O2-cannot be detected in the experimental assays due to the catalytic scavenging of superoxide radicals by Mn-SOD. In contrast to Cu,Zn-SOD, Mn-SOD is CN-resistant (1 1) but can be completely inhibited by 2% SDS (12) and 1 mM PHMB (25), and is partially sensitive to NaN3 (25). However, preliminary assays showed that only NaN3 did not inhibit XOD while both SDS and PHMB completely suppressed the activity of this 02-generating metalloenzyme.…”
Section: Resultsmentioning
confidence: 99%